The Effect of Shareholding on Dividends Obtained by The Regional Government of Sinjai Regency - Abidin, Zainal (Universitas Patria Artha, 2018)
ABSTRACTThe purpose of the company is to maximize the wealth of shareholders or owners of the company (wealth of the shareholders) .These normative objectives can be realized bymaximizing the market value of the company (market value of the firm) .To maximize the valueof the company can be achieved through the implementation of financial managementfunctions.This study aims to determine the effect of independent variables namely the ownershipof capital and the dependent variable is the dividend of Regional Government of Sinjai Regency.This research is descriptive quantitative. This research uses secondary data in the form offinancial statements obtained from PT. Bank Sulselbar branch of Sinjai Regency during theperiod 2012 to 2016. Data were analyzed by using multiple linear regression analysis. Theresult of the research showed that independent variable in the form of stock ownership hadpositive and significant effect to the dependent variable that was obtained by dividend ofGovernment of Sinjai Regency.